A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Sustainable integrated synthesis of high-yield and high-purity lignin-derived carbon dots: Dual-functional fluorescence detection and efficient chromatographic separation of nitro-antibiotics - Yuanmin Gong; Dan Wang; Panpan Chen; Renyu Deng; Meiting Yan; Baian Ji; Lingling Liu; Xueping Tao; Zhining Xia; Qifeng Fu (Food Chemistry, 2025)

Long-term toxicity evaluation of aristolochic acid-IIIa in mice - Lianmei Wang; Yuan Wang; Yong Zhao; Chunying Li; Yan Yi; Jingzhuo Tian; Guiqin Li; Zhong Xian; Fang Wang; Jing Meng; Yushi Zhang; Jiayin Han; et al. (Toxicology, 2024)

Circulation of Development Factors Promoted by Innovation of Land Management Under Background of Rural Vitalization: A Case Study of Tengtou Village in Zhejiang Province, China - Pengjun Wei; Yongqiang Liu; Jinlong Yan; Meiting Li; Yingnan Zhang (Chinese Geographical Science, 2023)

Enhancement of the chemical stability of nanoemulsions loaded with curcumin by unsaturated mannuronate oligosaccharide - Decheng Bi; Meiting Li; Lijun Yao; Nanting Zhu; Weishan Fang; Wushuang Guo; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Soy protein isolate-polyguluronate nanoparticles loaded with resveratrol for effective treatment of colitis - Wenhao Li; Decheng Bi; Jiang Yi; Lijun Yao; Jue Cao; Peng Yang; Meiting Li; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

A Deep Learning Method for NLOS Error Mitigation in Coastal Scenes - Chao Sun; Meiting Xue; Nailiang Zhao; Yan Zeng; Junfeng Yuan; Jilin Zhang (Journal of Marine Science and Engineering, 2022)
With the widespread use of automatic identification systems (AISs), some ships use deceptive information or intentionally close their AISs to conceal their illegal activities or evade the supervision of maritime departments. Although radar measurements can be effectively utilized to evaluate the credibility of received AIS data, the propagation of non-line-of-sight (NLOS) signal conditions is an important factor that affects location accuracy. This study addresses the NLOS problem in a special geometric dilution of precision (GDOP) scenario on a coast and several base stations. We employed data augmentation and a deep residual shrinkage network in order to alleviate the adverse effects of NLOS errors. The results of our simulations demonstrate that the proposed method outperforms other range-based localization algorithms in a mixed LOS/NLOS environment. For a special GDOP scenario with four radars, our algorithm’s root-mean-square error (RMSE) was lower than 180 m.

Regional water pollution management pathways and effects under strengthened policy constraints: the case of Tianjin, China - Yujia Wang; Mo Zhang; Chonggang Yang; Yan He; Meiting Ju (Environmental Science and Pollution Research, 2022)

The preparation of slow-release fertilizers with biomass ash and water/waste acid solutions from desulfurization and denitrification of flue gas - Yongfeng Qi; Ziqian Wang; Panle Ge; Meiting Wang; Chuanling Zhang; Huawei Wang; Lingzhi Zhao; Jiang Wu; Yan Li (Environmental Science and Pollution Research, 2022)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Temporal variability of seasonal warming rates in China - Chen Xu; Meiting Hou; Xiaodong Yan; Xianliang Zhang (International Journal of Climatology, 2021)
Calculation of the warming rate is the key to addressing the current debate about the existence of a recent hiatus in global warming. Previous studies have calculated the warming rate based on either a long period or selected periods. We calculated the warming rate in the seasonal temperatures obtained from 2,479 weather stations across China. We identified all the trend change years and divided the period 1958–2017 into different sub‐periods based on these years. Our results showed that the warming rate is higher than 0.5°C per decade in numerous stations. The amount of seasonal warming over the past 60 years was highest in winter, followed by spring, then autumn and was lowest in summer. Northern China has shown stronger warming than southern China over the past 60 years. Our results quantified the short‐period rates and identified natural change points which allows a sound comparison across regions. As rapid warming has a strong influence on natural systems and human health, extra care should be taken in regions with a high rate of warming.

A seasonal scale analysis correlating total cloud amount anomalies with ENSO over the tropical Pacific - Meiting Hou; Xiaodong Yan (Theoretical and Applied Climatology, 2011)